Carbon baby syndrome: A case report with review of literature - Sandhya Kumari; G K Verma; Anchana Gulati; Ajeet Negi (Wolters Kluwer Medknow Publications, 2024)
Carbon baby syndrome also known as universal acquired melanosis is one of the rare causes of diffuse and progressive hyperpigmentation of the skin. A case of a 9-year-old Nepali child was reported in whom darkening of the skin began at the age of 5 months. At presentation, generalized hyperpigmentation was observed with characteristic sparing of pressure areas over the palms and soles. The diagnosis was established by histopathological evidence of epidermal and dermal melanization after the exclusion of all cutaneous and systemic causes for such hyperpigmentation. This case is reported for its rarity and unusual clinicohistopathological features.